Nutrient uptake and removal by sweet potato fertilized with green manure and nitrogen on sandy soil - Fernandes, Adalton Mazetti [UNESP]; Assuncao, Natalia Silva [UNESP]; Ribeiro, Nathalia Pereira [UNESP]; Gazola, Bruno [UNESP]; Silva, Rudieli Machado da [UNESP] (Soc Brasileira De Ciencia Do Solo, 2020)
Sweet potato crops take up large amounts of nutrients, especially nitrogen. In low-fertility soils, the addition of nitrogen (N) increases the sweet potato yield. Green manure may be an alternative method for improving soil quality and supplying nutrients to this crop. This study aimed to evaluate the plant's nutritional status and the amount of nutrients taken up and removed by sweet potato plants subjected to green manure and mineral N fertilization. The experiment was carried out in the field for two growing seasons using a randomized block design in a split-plot scheme with four replications. The plots consisted of a control treatment (spontaneous weeds) and the previous cultivation of Crotalaria spectabilis and Mucuna aterrima. The subplots consisted of four N rates (0, 50, 100, and 200 kg ha(-1)) that were applied to the sweet potato. The species M. aterrima is more suitable for use as green manure in the sweet potato than C. spectabilis. Nitrogen application rates promoted a greater increase in the biomass of the storage root, nutrient uptake, and removal in the sweet potatoes unfertilized with green manure. In the sweet potato fertilized with M. aterrima, mineral N supply in excess (above 50 kg ha(-1)) increases the nutrient uptake and removal without a significant increase in the biomass of the storage root. In the sweet potatoes unfertilized with green manure, high rates of N (greater than 120 kg ha(-1)) must be applied to obtain the utmost biomass of the storage root, nutrient uptake and removal.
Keywords: Ipomoea batatas L.; nutritional demand; nutrient availability; root biomass; organic fertilization